Aplicações de fungicida para o controle da ferrugem asiática da soja e interações com diferentes arranjos espaciais da cultura - Ferreira, Marcelo Cigana (2009)
The control of Asian rust in soybeans depends, among other measures, on the rational use of fungicides. Spatial arrangements of plants that provide greater interception of light increases the potential for grain yield, but some of these arrangements hinder the application of fungicides. The objective was to evaluate the effects of plants populations and row spacings and their interactions with the application of fungicide timing and spray volume in the control of Asian rust and grain yield of soybean. Two experiments were conducted in the council of Tupanciretã-RS, the 2007-2008 growing season. In the first experiment was used 0,4 m spacing between rows and the populations 2x105, 3x105 e 4x105 plants.ha-1, where the fungicide applications were made at five application moments. The second experiment was planted with spacing of 0.40, 0.50 and 0.60 m between rows and population of 3x105 plants.ha-1, and the fungicide applied with five spray volumes. The experimental design was randomized blocks with split plots and three replications. The fungicide trifloxystrobin + cyproconazole was used at a dose of 0.3 L.ha-1 + mineral oil 0.5 L.ha-1. It was evaluated the incidence and severity of rust, the weight of thousand grains and grain yield. Data were submitted to analysis of variance and the Duncan test at 5% probability of error. There were significant interactions between plants populations and between spacing and timing and spray volume. Populations of 2x105 and 4x105 plants.ha-1, spraying before 10:30 am and after at 03:30 pm and spacings of 0.50 and 0.60 m between the lines and spray volume of 125 and 150 L.ha-1 provided the best results. It was concluded that there are viable combinations between plants arrangements and aspects of environmental conditions on the applications moment and spray volumes to enable improvements in rust control, as well in increasing the soybean grain yield